178. Trial prospettico per predire la correlazione dose risposta nei muscoli costrittori faringei in pazienti con tumore testa-collo Prospective trial to predict the pharyngeal constrictor muscle dose-response correlation in head and neck cancer patients. (December 2018) - Di Dia, A.; Strigari, L.; Bresciani, S.; Maggio, A.; Miranti, A.; Strolin, S.; Delmastro, E.; Gabriele, D.; Gabriele, P.; Stasi, M.
Abstract: Purpose: Radiotherapy, alone or combined with chemotherapy, is a treatment modality used frequently in head and neck cancer. It is important to delineate organs in the head and neck at risk for radiation-induced swallowing dysfunction (RISD). Irradiation of the Pharyngeal Constrictor Muscle (PSCM) seems to play a crucial role in swallowing dysfunctions and in particular in the voice and speech quality changes. Purpose of our retrospective study was to identify which dose volume histogram parameters are most important to predict patient radiation-induced swallowing dysfunction, voice and speech quality. Methods: Patients with head and neck cancer who previously underwent Tomotherapy treatment are selected. The prescribed radiotherapy is based on SIB technique for all PTVs irradiated simultaneously over 30 daily. Doses of 67.5, 60 and 54–57 Gy were prescribed to primary tumour, high-risk nodal regions and low-risk nodal regions, respectively. Upper PSCM, middle PSCM and lower PSCM were outlined separately and DVHs are stored for each patient using basal planning CT and weekly MVCT. Univariate and multivariate analysis will be used to identify novel dosimetric predictors of toxicity and predictors of quality of life assessed using appropriate questionnaires taking into consideration the actual delivered dose. Results: The study started in July 2017 and the up to now 8 patients have been included in the study. Preliminary results suggest the importance of taking into consideration the dosimetric information based on basal planning CT and MVCT in order to improve the evaluation of toxicity rate and occurrence, which are still ongoing. Conclusions: Dosimetric factors based on planning CT and MVCT seem to improve the identification of appropriate predictors of toxicity. More patients are to be included in the study to fully confirm these preliminary results.